2016
DOI: 10.3389/fmicb.2016.00616
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Oxamyl-degrading Bacteria and Identification of cehA as a Novel Oxamyl Hydrolase Gene

Abstract: Microbial degradation is the main process controlling the environmental dissipation of the nematicide oxamyl. Despite that, little is known regarding the microorganisms involved in its biotransformation. We report the isolation of four oxamyl-degrading bacterial strains from an agricultural soil exhibiting enhanced biodegradation of oxamyl. Multilocus sequence analysis (MLSA) assigned the isolated bacteria to different subgroups of the genus Pseudomonas. The isolated bacteria hydrolyzed oxamyl to oxamyl oxime,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…It has been demonstrated before that minor amino acid substitutions can have determining effects on an enzyme's activity and substrate preference. In the case of melamine deaminase TriA and atrazine chlorohydrolase AtzA, a difference of only nine amino acids exists between these two enzymes but AtzA cannot recognize melamine and TriA cannot recognize atrazine (Seffernick et al, 2001). As for CfdJ, one amino acid change from glutamine in AtzA to aspartate in TriA at residue 125 has a determining effect on the enzyme's activity (dechlorination vs deamination) (Noor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated before that minor amino acid substitutions can have determining effects on an enzyme's activity and substrate preference. In the case of melamine deaminase TriA and atrazine chlorohydrolase AtzA, a difference of only nine amino acids exists between these two enzymes but AtzA cannot recognize melamine and TriA cannot recognize atrazine (Seffernick et al, 2001). As for CfdJ, one amino acid change from glutamine in AtzA to aspartate in TriA at residue 125 has a determining effect on the enzyme's activity (dechlorination vs deamination) (Noor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Between AtzA and TriA, just like in the case of CfdJ and CehA, only a single silent mutation is evident. This indicates that a strong selection pressure leads to the rapid changes in the amino acid composition that enables the organism to adapt to new substrates (Seffernick et al, 2001) as weak selection pressure often yields silent mutations that correct for codon bias (Jukes, 1980;Akashi, 1999). Noor et al (2014) recently showed that evolution of AtzA is ongoing by identifying AtzA homologues in different triazine degrading bacteria in which single amino acid substitutions determined triazine substrate range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer-lipid and other hybrid nanomaterials possessing different material properties such as hydrophobicity and water solubility should also be studied for SPs (Byrappa et al, 2008; Wu et al, 2012). Although the effect of soil applied pesticides on soil microbial community structure and rhizo-epiphytic microorganisms has been extensively studied, the effects on endophytic consortium and seed microbiome have to be studied further (Karpouzas et al, 2016; Rousidou et al, 2016). Knowledge on the interaction of SPs with endophytic microorganisms and their enzymatic activity can improve the efficacy of existing or new pesticides.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Four different strains of Pseudomonas were isolated from soil exhibiting enhanced oxamyl biodegradation. Bacteria could transform oxamyl to oxamin oxime by utilizing methylamine as a source of C and N. All of the four strains carried carbamate hydrolase homologue of the cehA gene (Rousidou et al, 2016). Carbamyl degrading bacteria; Bacillus, Morganella, Pseudomonas, Aeromonas and Corrynebacterium were isolated from local soil ecosystem of the Gaza strip.…”
Section: Biodegradation Of Carbamatementioning
confidence: 99%